Islamic Religious Education Teachers' Strategies in Increasing Students' Interest in Learning at SMPN 7 South Konawe - Dirman; Asrianti (Dirasah: Jurnal Pendidikan Islam, 2025)
This research aims to analyse the strategies implemented by Islamic Religious Education teachers in increasing students' interest in learning at SMPN 7 South Konawe. In the educational context, interest in learning is an important factor that can influence the success of the learning process, especially in religious lessons which are often considered less interesting by some students. This research uses a qualitative approach with a case study method involving direct observation, interviews with Islamic Religious Education teachers, school principals and students. The data obtained was analysed descriptively to identify various strategies used by teachers, as well as factors that support and hinder increasing student interest in learning. The research results show that the strategies implemented by teachers include an active learning approach, the use of interesting learning media, and providing motivation through positive reinforcement. Apart from that, students' internal factors, such as personal motivation and family support, also play an important role in increasing their interest in learning. However, there are several obstacles, such as a lack of supporting facilities and challenges in managing heterogeneous classes. It is hoped that this research can contribute to the development of more effective learning strategies in increasing students' interest in learning, especially in Islamic Religious Education lessons at SMPN 7 South Konawe.